proaíresis pneúmatos im LXX-Ekklesiastes: LXX - Daphnē, Euangelia (Journal for semitics, 2024)
This article examines all evidence of the word combination προαίρεσις πνεύματος, which represents a linguistic and intellectual peculiarity of the LXX Ecclesiastes. It explains in which way the choice of words and the stylistic devices of the LXX translator, who is also a poet, puts into context the relation of προαίρεσις πνεύματος in LXX Ecclesiastes to Genesis 2-3 (serpent) and Job 1-2 (Satan), as well as to 1Sam 16:14 etc. (evil spirit), 1Kgt 22:19-23 par. 2Chr 18:18-22 (lying spirit) and Zach 13:2 (unclean spirit) and traces the vanity and nothingness in this world back to the purpose of the spirit.